(untitled) (Journal of Parents and Teachers, 1995)
The article addresses the complexity of giving recommendations to children, highlighting how external influences and the use of privilege can affect their decisions. It criticizes society’s manipulation of young people, and the importance of an education based on empathy and understanding, emphasizing the role of theater as an essential educational tool.